Views on Conflict related to the Causes of Conflict and the Management Strategies - Dermaku, Armando; Balliu, Erost (International Journal Papier Public Review, 2021)
This article discusses the views of conflict related to the factors causing conflict and conflict management strategies. The results of the discussion show that other potential sources of conflict are personal factors which include the value system that each individual has, personality characteristics that cause individuals to be unique and different from other individuals. The fact shows that certain personality types, such as individuals who are very authoritarian, dogmatic, and have low regard for others, are potential sources of conflict. If one of these conditions occurs in a group, and employees are aware of it, then the perception arises that in the group there is a conflict. Each group has different goals and each strives to achieve them. This problem occurs because when groups become more attached to their own goals or norms. This situation is called perceived conflict. The problem solving strategy in conflict is the basic assumption that all parties have a desire to handle the conflict that occurs and therefore it is necessary to find measures that can satisfy the parties involved in the conflict. On the basis of these assumptions, the problem solving strategy must always go through two important stages, namely the process of finding ideas and the process of maturing them.